From the back room to the front room: Combining clinical and financial information to support evidence-based decision making - Robertson, Nathalie; Loreti, Marcus (International Journal of Population Data Science, 2018)
Introduction Decisions in healthcare are not based on a single piece of evidence. Decision-makers consider a broad range of information, including patient, system and financial information. Canadian healthcare decision-makers now have access to linked clinical and financial data – at the patient level - via an online, private tool. Objectives and Approach The objectives of this presentation are to showcase the power of having linked inpatient and ambulatory care clinical and financial data, as presented in an online tool. More specifically, two separate scenarios will be worked through, demonstrating how key decisions can be impacted by having record-level clinical and financial information. For example, a hospital may make a different decision when looking at the price differential of performing some surgeries and keeping patients overnight, versus performing these same surgeries in day surgery context and sending patients home. Supporting drill-down detail and visualizations will also be showcased. Results The presentation will focus on the importance of leveraging and integrating available information to better support decision-making. The presentation will emphasize how this tool, which uses linked clinical and financial data, is an example of the integration of new information sources into traditional decision-making practices. For example, with the availability of detailed cost estimates tied to clinical information, decision-makers have the ability to provide budgeting and costing estimates, by area, for different patient types. This is particularly important for health organizations that do not have a patient costing system in place. Conclusion/Implications Tools that integrate information in an easy to use format allow decision-makers to access important information quickly, thus facilitating more time to gather supplemental information and consider the information at hand, ultimately supporting evidence-based decision-making.